Model Kepemtensi Tenaga Administrasi Sekolah Menengah Kejuruan - Lantip Diat Prasojo (Dinamika Pendidikan, 2008)
Vocational High School Administrative Personnel Profession enough having immeasurable and requires expertise area and different education' ladder also" causing requires different competence for every the work type. Besides, characteristic areas in Indonesia different causes Vocational High School has characteristic differing from materialization of formula vision and mission which is also different. There/ore, Administrative personnel competence demands. each Vocational High School of course different causing is required an formulation of Administrative Personnel Competence model for Vocational High School. ·In formulating Administrative Personnel Competence Vocational High School must include cover four things following: a) refers to vision and mission Vocational High School, b) based on at fundamental duty and function of Administrative Personnel Vocational High School, c) based on at reasoning of education required as according to its (the duty), d) existence of process controller system which in the form oj quality oj service as a means of measure success of the formula process. Keyword: competence, Voeatlonal High School Administrative Personnel